Pengaruh Model Pembelajaran Mind Mapping dan Motivasi Terhadap Hasil Belajar Siswa Mata Pelajaran Ekonomi di SMA N I Tanjung Raya - Hilda Sri Dewita; Syamsul Amar (Jurnal Kajian Pendidikan Ekonomi, 2014)
The aims of this research was to reveal (1) the difference between economy learning outcomes of the students who were taught by using learning model mind mapping and those who were taught by using conventional model, (2) the difference between economy learning outcomes of the students who had high motivation and were taught by using learning model mind mapping and those who also had high motivation but were taught by using conventional model, (3) the difference between economy learning outcomes of the students who had low motivation and were taught by using learning model mind mapping and those who also had low motivation but were taught by using conventional. (4) the interaction between learning model and motivation toward economy students learning outcomes. The population of this research was all of the first year students at SMA Negeri 1 Tanjung Raya which consisted of 6 classes, each class had 170 students.  The samples by using cluster random sampling technique. The researcher chose the experimental class is X.4 and as the control class is X.1. This research was a quasi experimental which used 2x2 factorial design. The data then was analyzed by using t-test and Anava. The result of research showed that: (1) learning outcomes of the students who were taught by using learning model mind mapping was higher than those who were taught by using conventional model, (2) learning outcomes of the students who had high motivation and were taught by using learning model mind mapping was higher than those who also had high motivation but were taught by using conventional model, (3) learning outcomes of the students who had low motivation and were taught by using learning model mind mapping was higher than those who also had low motivation but were taught by using conventional model, and (4) there was not interaction between learning model and motivation toward students learning outcomes.   Keywords: Learning Model, Mind Mapping, Motivation, Learning Outcomes, Economy